Effect of Dose Biochar Bamboo, Compost, and Phonska on Growth of Maize (Zea mays L.) in Dryland - Situmeang, Yohanes Parlindungan; Adnyana, I Made; Netera Subadiyasa, I Nengah; Merit, I Nyoman (International Journal on Advanced Science, Engineering and Information Technology, 2015)
The purpose of this study was to determine the effect of treatment of various doses of biochar level bamboo, compost, and phonska on hybrid corn plant growth bisi-2 super in dry land. The design used in this study is a randomized block design (RAK) with a pattern of nested experiments. Factors treatment consists of 3 types of materials to improve soil quality, that biochar bamboo, organic compost fertilizer and inorganic fertilizer dose phonska with 4 levels and a control for comparison. The results showed that the treatment of the type of fertilizer had no significant effect on all the variables observed. While the dosage of biochar bamboo gives highly significant effect on plant height, number of leaves and total leaf area per plant. The highest result of variable plant height, number of leaves and total leaf area per plant corn obtained at treatment dose of 5-10 tons/ha biochar bamboo, 10-20 tons/ha of compost and 300 kg/ha phonska. From the results of the regression analysis obtained optimum doses of biochar bamboo 10.93 tonnes/ha with maximum plant height of 244.11 cm, the optimum dose of compost 19.54 tonnes/ha with maximum plant height of 247.89 cm, and the optimum dose phonska 308.11 kg/ha with a plant height of 246.32 cm.